A new species of Spelaeogammarus (Amphipoda: Bogidielloidea: Artesiidae) with an identification key for the genus - Bastos-Pereira, Rafaela; Ferreira, Rodrigo L. (Zootaxa, 2015)
There are five described species of the cave-dwelling amphipods of the genus Spelaeogammarus, all of them inhabiting caves on the Brazilian state of Bahia. A new species of this genus is here described, which is closely related to the already known species S. santanensis and S. titan. Spelaeogammarus sanctus sp. nov. differs from its congeneric species basically by the presence of more than 18 bifid setae on the dorsal margin of uropod 3 outer ramus and telson with one apical and two subapical stout setae, while the other species generally present less setae on the third uropod and more setae on telson. An identification key and an updated table of the Spelaeogammarus species diagnosis are provided, as well as a multivariate statistical approach of morphological variations among the species.